El muro de La Separación: ¿racismo u ocupación? - Alloush, Ibrahim (Revista de Estudios Árabes, 2014)
Professor Ibrahin Alloush affirms that the Wall is just the continuation of the Zionist project that started a century ago, the judaization of Palestine. Through it, around 45% of the land will be under Israeli control permanently. The real aim is two-fold: encourage Jewish immigration, and control of the land followed by expulsion of the Palestinian population. The effects of the Wall will result in poverty and hunger, forcing many residents to emigrate or move elsewhere in Palestine.